The Influence of Involvement in Behaviour Problems on Learners’ Academic Performance in Nairobi County, Kenya - Ong’era, Lynett Kemunto (IJRDO- Journal of Educational Research, 2016)
This study sought to determine the influence of involvement in behaviour problems on learners’ academic performance in Nairobi County, Kenya. There is abundant evidence to support the correlation between children’s behaviour problems and academic performance. Behaviour problems are exhibited by learners of different ages and educational levels and interfere with learning, development and also negatively affect those around the learner’s environment. They may include aggression, drug and substance abuse and teenage sex, among others. These behaviour problems significantly affect learners’ academic performance and hence academic achievement. Further, behavioural problems interrupt academic progress and create conditions that make it difficult to achieve educational objectives. Findings of this study revealed that overall academic performance of learners who were involved in behaviour problems was significantly lower than those who were not involved in behaviour problems.